Perceptions of fatigue and neuromuscular measures of performance fatigability during prolonged low‐intensity elbow flexions. Issue 3 (10th February 2023) - Marzouk, Monica; McKeown, Daniel J.; Borg, David N.; Headrick, Jonathon; Kavanagh, Justin J.
Abstract : New Findings: What is the central question of this study? What is the predictive relationship between self‐reported scales to quantify perceptions of fatigue during exercise and gold standard measures used to quantify the development of neuromuscular fatigue? What is the main finding and its importance? No scale was determined to be substantively more effective than another. However, the number of ongoing contractions performed was shown to be a better predictor of fatigue in the motor system than any of the subjective scales. Abstract: The purpose of this study was to determine the relationship between transcranial magnetic stimulation (TMS) measures of performance fatigability and commonly used scales that quantify perceptions of fatigue during exercise. Twenty healthy participants (age 23 ± 3 years, 10 female) performed 10 submaximal isometric elbow flexions at 20% maximal voluntary contraction (MVC) for 2 min, separated by 45 s of rest. Biceps brachii muscle electromyography and elbow flexion torque responses to single‐pulse TMS were obtained at the end of each contraction to assess central factors of performance fatigability. A rating of perceived exertion (RPE) scale, Omnibus Resistance scale, Likert scale, Rating of Fatigue scale and a visual analogue scale (VAS) were used to assess perceptions of fatigue at the end of each contraction. The RPE (root mean square error (RMSE) = 0.144) and Rating of Fatigue (RMSE = 0.145) scales were the best predictors of decline in MVC torque, whereas the Likert (RMSE= 0.266) and RPE (RMSE= 0.268) scales were the best predictors of electromyographic amplitude. Although the Likert (RMSE = 7.6) and Rating of Fatigue (RMSE = 7.6) scales were the best predictors of voluntary muscle activation of any scale, the number of contractions performed during the protocol was a better predictor (RMSE = 7.3). The ability of the scales to predict TMS measures of performance fatigability were in general similar. Interestingly, the number of contractions performed was a better predictor of TMS measures than the scales themselves.